Challenges for Creating Resilience in Minorities and Female Workers, and the Role of Flexibility in Work Environments: A Mixed Method Study - Dawn Adams-Harmon; Aleisha Lewis; Jung Ah (Claire) Yun (SocioEconomic Challenges)
Prior to the COVID-19 pandemic, remote and hybrid work options were scarcely available. Where applicable, workers experienced remote and flexible hybrid work arrangements, during the pandemic. Post-pandemic, many companies are pivoting and rescinding remote and hybrid options and requiring in-office attendance. The impetus of this research was to ascertain future workers’ preferences for remote, hybrid, and live work situations. The challenge is that current students have become accustomed to flexible work and school standards. This mixed method research was conducted with 289 undergraduate business students studying online and on-campus in an urban University in at an urban University, Kean University in Union, New Jersey, in May and September of 2023. Open-ended and Likert scale survey questions were given anonymously to undergraduate business students, with a 72.3% response rate. The following quantitative hypotheses were researched and should be significant: H1: Gender (Women vs. Men) - female students may perceive workplace flexibility more importantly than male students. H2: Racial/Ethnic Minority - racial/ethnic minority students may value workplace flexibility more than white students. H3: Intersectionality - racial/ethnic minority female students may perceive workplace flexibility as more important than other students. In terms of the qualitative findings, the results uncovered that female and racial/ethnic minority students regard flexible work arrangements, such as hybrid work, more importantly than others. Females and racially diverse employees desire greater flexibility to maintain work-life balance. Lastly, female students perceive work-life balance very differently from male students. The benefits to workers include decreased commuting costs, increased commitment, and decreased stress, while employers benefit by keeping attrition levels low, increasing employee engagement, and decreasing office space requirements and associated overhead costs while maintaining productivity. The challenge for employers is to continue to offer flexible work options instead of eliminating them, particularly if a corporation desires to increase the number of females and racially diverse employees at their companies.